Standardization of the Typical Sakura Cake Recipe for Jorong Cangkiang Nagari Batu Taba - Salsabila, Shofira; Syarif, Wirnelis; Fridayanti, Lucy; Siregar, Juliana (Universitas Negeri Padang, 2024)
This research was motivated by the lack of standardization of Kue Sakura recipe. This can be seen in the results of observations of material preparation techniques and manufacturing methods, so that the resulting quality is not the same. And of course this research aims to find a standard recipe for Kue Sakura. This type of research is a mixed method, namely combining quantitative research with qualitative research. This research will be carried out in Jorong Cangkiang Nagari Batu Taba in January - February 2024. Based on the results of standard organoleptic tests for Kue Sakura recipes which have been converted with 3 repetitions, it was found that the quality of kue Sakura is seen from its tube-like shape, light yellow color, soft texture, typical vanilla aroma and sweet taste.